Behavior Analysts' Use of and Beliefs in Treatments for People with Autism: A 5‐Year Follow‐up. (13th October 2016) - Schreck, Kimberly A.; Karunaratne, Yenushka; Zane, Thomas; Wilford, Heather
Abstract : As autism prevalence rises, parents of children with autism rely upon professionals to recommend the most effective treatment for their children. Historically, these professionals have chosen a range of treatments from empirically supported to nonempirically supported treatments. This study replicated and extended that work by surveying Board Certified Behavior Analysts to determine what treatments they promoted and used. Results showed that although most respondents used evidence‐based, behavioral procedures, many did not. Influential stimuli most likely to contribute to behavior analysts' choices of treatments were beliefs in effectiveness, ease of implementation, and persuasion by others. Self‐reported reinforcers for treatment use included perceived observed success, praise from others, and financial gain. Behavior analysts continue to use a variety of nonscientifically supported treatments, including those that have been deemed ineffective and harmful to people with autism. Future training of Board Certified Behavior Analysts must stress adherence to the ethical code for certified behavior analysts, adherence to data‐based decision‐making, and strict fealty to the scientific process in which all behavior analysts have been trained. Copyright © 2016 John Wiley & Sons, Ltd.